Anorectal malformations in males: Pros and cons of neonatal versus staged reconstruction for high and intermediate varieties - Prema Menon; Katragadda Lakshmi Narasimha Rao; Amit Kumar Sinha; K Lokesha; Ram Samujh; Jai Kumar Mahajan; Ravi Prakash Kanojia; Monika Bawa (Wolters Kluwer Medknow Publications, 2017)
Background: High and intermediate types of anorectal malformations (ARMs) in male neonates may be managed either by primary neonatal reconstruction without colostomy cover or by traditional policy of staged reconstruction after neonatal colostomy. Posterior sagittal anorectoplasty (PSARP) is the current widely practiced reconstructive technique with varied results. Aim: To assess our functional results of PSARP without colostomy in male neonates with high and intermediate ARMs compared to 3-stage (neonatal colostomy - PSARP - colostomy closure) methodology in a high volume tertiary care institution of a developing country. Patients and Methods: The number of colostomies performed for male high/intermediate anomalies and the number of babies who completed 3-stage reconstruction during a 10-year period is analyzed. The outcome of primary neonatal PSARPs during the same period was analyzed. Eighty primary PSARPs were compared to 81 staged reconstructions for outcome analysis, using Kelly score. Results: A total of 453 colostomies were performed, but only 253 of them completed all stages of reconstruction (52%). Good continence was achieved in 45% of cases of primary PSARP versus 26% in 3-staged surgery. Conclusions: Primary PSARP in neonatal period without colostomy is a good option for high and intermediate ARMs in males if the treating surgeon is reasonably skilled in neonatal surgery and PSARP procedures.